(untitled) (One Health & Risk Management, 2023)
Introduction. The doping phenomenon remains a significant and current issue in professional sports worldwide, posing a hazard to public health as it extends into amateur sports. Recent research conducted for the NARD-TUBITAK project, titled “Capacity building of Anti-doping Research and Collaboration through Initiatives in Medical Education” (2021–2022), has exposed gaps in anti-doping education and knowledge regarding athletes’ nutrition, including diet and supplement use. These findings provide a basis for the current project proposal. The past two years, marked by lockdowns, restrictions on physical activity, and the Covid-19 outbreak, have presented severe challenges to athletes and the general youth population. These challenges have encouraged individuals to adopt risky behaviors in an attempt to recover quickly. This environment has set the stage for increased usage of performance-enhancing pharmaceuticals and/or nutritional supplements with the aim of improving sports performance. Material and methods. An international collaborative network was established between the Republic of Moldova and Turkey, resulting in the development of the project "Common Actions in Anti-Doping Research through Piloting of Innovative Interventions in Education." The project aims to sustain bilateral cooperation between Moldova and Turkey on anti-doping issues and enhance medical and public knowledge regarding the doping phenomenon. The project’s purpose is to transfer knowledge and cultivate shared perspectives among Turkish and Moldovan researchers and public entities in the areas of education and awareness. Subsequently, the project seeks to identify interventions necessary for the prevention of doping among the youth. Communication, dissemination, skill development, and knowledge sharing are integral components of the project. Results. The extension of anti-doping cooperation, the identification of health needs in this area, and the development of strategies as solutions or preventative measures constitute the primary elements of this collaboration. The delay in implementing anti-doping initiatives at the national level hampers progress and research in anti-doping issues. Addressing these challenges will support the augmentation of resources for universities and anti-doping agencies and promote knowledge regarding the use of nutritional supplements. Cross-country cooperation will facilitate the resolution of specific problems for two countries with different needs. Medical doctors from the Republic of Moldova will directly benefit from a new type of working experience—"learning through research"—in accordance with international regulations. In the long term, this bilateral collaboration is poised to lead to the development of research and communication programs on the European scale. The project will contribute to providing more data regarding anti-doping knowledge in the Republic of Moldova. Additionally, the partnership with the Republic of Moldova will create opportunities to share Turkey’s experiences in doping prevention. Conclusions. Collaboration and partnership bring benefits to both countries as they fully align with the research recommendations of the World Anti-Doping Agency (WADA). These recommendations focus on the development of prevention models, addressing non-sport influences, promoting clean sport behaviors, and understanding the role and influence of anti-doping support personnel. Note: The study was carried out with the support of the Moldovan-Turkish bilateral research and innovation project 23.80013.0807.4TR "Common Actions in Anti-Doping Research through Piloting of Innovative Interventions in Education".